1999
DOI: 10.1021/ja9841005
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase Activity of Myoglobin Is Enhanced by Chemical Mutation of Heme-Propionates

Abstract: Peroxidase activity of a myoglobin reconstituted with a chemically modified heme 1 is reported. The heme 1 bearing a total of eight carboxylates bound to the terminal of propionate side chains is incorporated into apomyoglobin from horse heart to obtain a new reconstituted myoglobin, rMb(1), with a unique binding domain structure. The UV−vis, CD, and NMR spectra of rMb(1) are comparable with those of native myoglobin, nMb. The mixing of rMb(1) with hydrogen peroxide yields a peroxidase compound II-like species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 19 publications
3
74
0
4
Order By: Relevance
“…S8), which indicated that the site specific polymer conjugation of Mb at the N-terminus through in situ ATRP did not perturb the tertiary structure of the protein. We further confirmed the retention of the functional activity of the conjugate by quantifying the peroxidase-like activity of Mb (31). The absorbance at 409 nm was monitored by UV-visible spectrophotometry after treatment of Mb and modified derivatives with 2,2 ' -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) following reaction with hydrogen peroxide (Fig.…”
Section: Purification and Characterization Of Mb-n-poly(oegma)supporting
confidence: 60%
“…S8), which indicated that the site specific polymer conjugation of Mb at the N-terminus through in situ ATRP did not perturb the tertiary structure of the protein. We further confirmed the retention of the functional activity of the conjugate by quantifying the peroxidase-like activity of Mb (31). The absorbance at 409 nm was monitored by UV-visible spectrophotometry after treatment of Mb and modified derivatives with 2,2 ' -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) following reaction with hydrogen peroxide (Fig.…”
Section: Purification and Characterization Of Mb-n-poly(oegma)supporting
confidence: 60%
“…The same mechanism can be followed by Mb, which is known to oxidize phenolic compounds to radical species (107). As for peroxidases, both the two protein intermediates generated by Mb upon reaction with H 2 O 2 can oxidize catechols to the corresponding radicals (108). These reactive species can diffuse into the solution, in which they can undergo a sequence of reactions leading to oligomerization (reactions 9-11): In competitive processes, dopamine semiquinone and DAQ can interact with amino-acid residues.…”
Section: Heme-protein Modification By Catecholsmentioning
confidence: 99%
“…Many improvements have occurred regarding nanoparticles synthesis with exact sizes and specific characteristics (1). The most essential parts of nanotechnology are comprehensive understanding of nanoparticles interaction with proteins, and response of biological systems for analysis of nano medicine and nano biotechnology experimental results (2).…”
Section: Introductionmentioning
confidence: 99%
“…Forming a corona is a competitive process, and these entities start to grow in biological solutions quickly and upon the clash of nanoparticles with proteins and under influence of hydrodynamic, electrodynamics and electrostatic forces (9,10). The created corona quickly becomes complete in a way that at first the proteins with high concentration absorb quickly to these particles, yet during the time lapse their positions are substituted with those proteins, which have the highest tendency (1,11). These particles can have deep impacts on the proteins at conformation and performance levels, protein tertiary structure (by decoration of a helixes and beta sheets), compact construction of the central hydrophobic amino acids, a sharp reduction in entropy and electrostatic repulsion are controlled; the reaction of the protein with the charged levels and interaction with foreign forces can make some changes in the three dimensional structure of the protein (12,13).…”
Section: Introductionmentioning
confidence: 99%